Wine consumers’ preferences in Spain: an analysis using the best-worst scaling approach - de-Magistris, Tiziana; Gracia, Azucena; Albisu, Luis-Miguel (Spanish Journal of Agricultural Research, 2014)
Research on wine consumers’ preferences has largely been explored in the academic literature and the importance of wine attributes has been measured by rating or ranking scales. However, the most recent literature on wine preferences has applied the best-worst scaling approach to avoid the biased outcomes derived from using rating or ranking scales in surveys. This study investigates premium red wine consumers’ preferences in Spain by applying best-worst alternatives. To achieve this goal, a random parameter logit model is applied to assess the impacts of wine attributes on the probability of choosing premium quality red wine by using data from an ad-hoc survey conducted in a medium-sized Spanish city. The results suggest that some wine attributes related to past experience (i.e. it matches food) followed by some related to personal knowledge (i.e. the designation of origin) are valued as the most important, whereas other attributes related to the image of the New World (i.e. label or brand name) are perceived as the least important or indifferent.